Are tactile function and body awareness of the foot related to motor outcomes in children with upper motor neuron lesions? - Marsico, Petra; Meier, Lea; van der Linden, Marietta L.; Mercer, Thomas H.; van Hedel, Hubertus J. A. (Frontiers in Rehabilitation Sciences, 2024)
Introduction: Somatosensory function can be reduced in children with Upper Motor Neuron (UMN) lesions. Therefore, we investigated relationships between somatosensory functions of the foot and motor outcomes in children with UMN lesions.In this cross-sectional study, we assessed the Tactile Threshold (TT) with monofilaments and body awareness with Tactile Localisation Tasks for spatial-related action (TLTaction) and structural-related perception (TLTperception) body representation at the foot sole. Furthermore, we assessed four motor outcomes: the Selective Control Assessment of the Lower Extremity (SCALE), the modified Timed Up and Go test (mTUG), the Gillette Functional Assessment Questionnaire (FAQ), and the Functional Mobility Scale (FMS). Spearman's correlations (ρ) were applied to assess relationships between the somatosensory function of the foot sole and the applied motor outcomes.Results: Thirty-five children with UMN lesions, on average 11.7 ± 3.4 years old, participated. TLTperception correlated significantly with all lower limb motor outcomes p<0.05),. TLTperception correlated strongly with the Gross Motor Function Classification System (|ρ|=0.62; p=0.001) in children with cerebral palsy (n=24).Discussion: Assessing structural body representation of the foot sole should be considered when addressing lower limb motor impairments, including gait, in children with upper motor neuron lesions. Our results suggest that the assessment of tactile function and spatial body representation may be less related to lower limb motor function.